2006
DOI: 10.1103/physrevb.74.134404
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization dynamics of the ferrimagnet CoGd near the compensation of magnetization and angular momentum

Abstract: Magnetization dynamics in alloys of ferrimagnetic CoGd have been studied in the vicinity of the magnetization and angular momentum compensation point as a function of alloy composition and temperature. In agreement with standard mean-field treatments of the dynamics of the total magnetization we observe an increase of the precessional frequency and the effective damping parameter near the angular momentum compensation point. We demonstrate the consistency of the magnetization dynamics extracted from frequency … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
90
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 17 publications
12
90
2
Order By: Relevance
“…Based on the expression above, our TbCo composition is expected to have T M < T A considering the g factors of Co (∼2.2) and Tb (∼1.5) [47,48] and the weak temperature dependence of the Co sublattice magnetization in the measurement range. The difference between T M and T A is ∼50 K for GdFeCo [35] and ∼80 K for GdCo [36], and our TbCo is expected to show a greater temperature difference, with T A > 300 K. Jiang et al reported current-induced switching (CIS) of a spin-valve system using a CoGd free layer and found that magnetoresistance and CIS showed different temperature dependence [39], with the former showing an anomaly near T M and the latter near T A . Our results do not indicate any obvious anomalies in either spin transport or SOTs other than near T M .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the expression above, our TbCo composition is expected to have T M < T A considering the g factors of Co (∼2.2) and Tb (∼1.5) [47,48] and the weak temperature dependence of the Co sublattice magnetization in the measurement range. The difference between T M and T A is ∼50 K for GdFeCo [35] and ∼80 K for GdCo [36], and our TbCo is expected to show a greater temperature difference, with T A > 300 K. Jiang et al reported current-induced switching (CIS) of a spin-valve system using a CoGd free layer and found that magnetoresistance and CIS showed different temperature dependence [39], with the former showing an anomaly near T M and the latter near T A . Our results do not indicate any obvious anomalies in either spin transport or SOTs other than near T M .…”
mentioning
confidence: 99%
“…Hence, our results for the SOT effective field are particularly surprising and unexpected. Previously, Stanciu et al [35] and Binder et al [36] have demonstrated ultrafast switching as well as a divergence of the damping constant near T A (not T M ) using optical pump probe and vector network analyzer-ferromagnetic resonance techniques. While at…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that AHE sign dramatically changes as the Tb composition varies. 24 Thus, even slight decrease of Tb composition results in AHE sign change. The hysteresis as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%